RBM10 Regulates Tumor Apoptosis, Proliferation, and Metastasis - Cao, Yingshu; Di, Xin; Zhang, Qinghua; Li, Ranwei; Wang, Ke (Frontiers in Oncology, 2021)
The RNA-binding motif protein 10 (RBM10) is involved in alternative splicing and modifies mRNA post-transcriptionally. RBM10 is abnormally expressed in lung, breast, and colorectal cancer, female genital tumors, osteosarcoma, and other malignant tumors. It can inhibit proliferation, promote apoptosis, and inhibit invasion and metastasis. RBM10 has long been considered a tumor suppressor because it promotes apoptosis through the regulation of the MDM2-p53 negative feedback loop, Bcl-2, Bax, and other apoptotic proteins and inhibits proliferation through the Notch signaling and rap1a/Akt/CREB pathways. However, it has been recently demonstrated that RBM10 can also promote cancer. Given these different views, it is necessary to summarize the research progress of RBM10 in various fields to reasonably analyze the underlying molecular mechanisms, and provide new ideas and directions for the clinical research of RBM10 in various cancer types. In this review, we provide a new perspective on the reasons for these opposing effects on cancer biology, molecular mechanisms, research progress, and clinical value of RBM10.